THE RELATIONSHIP BETWEEN PARITY AND HYPEREMESIS GRAVIDARUM IN PREGNANT WOMEN AT THE SUKODONO PUBLIC HEALTH CENTER, LUMAJANG REGENCY IN 2025 - Dona Desy Ani Candra; Wahida Yuliana; Farianingsih (The Shine Cahaya Dunia Kebidanan, 2026)
Background: Hyperemesis gravidarum tends to be more common in women experiencing their first pregnancy or in women with high parity, such as those experiencing their fourth or more pregnancies. This condition can be influenced by psychological factors, such as anxiety or fear of the responsibilities of motherhood, especially when feeling unable to care for existing children. This type of mental stress can lead to emotional conflict that worsens nausea and vomiting during pregnancy. The purpose of this study was to analyze the relationship between parity and hyperemesis gravidarum in pregnant women at the Sukodono Community Health Center in Lumajang Regency in 2025. Methods: The research design is a plan or plan created by the researcher as a framework for the activities to be implemented. This study employed a cross-sectional design. The population included all 34 pregnant women with hyperemesis gravidarum at the Sukodono Community Health Center, who also served as the research sample. Results: The results of the rho test indicated a p-value of 0.00 with a significance level (α) <0.05. Because the p-value is smaller than α, H₀ is rejected and H₁ is accepted. This indicates that there is a relationship between parity and hyperemesis gravidarum in pregnant women at the Sukodono Community Health Center, Lumajang Regency in 2025. Conclusion: The results of this study indicate a relationship between parity and hyperemesis gravidarum in pregnant women at the Sukodono Community Health Center, Lumajang Regency in 2025.